ANALISIS FAKTOR-FAKTOR KINERJA PEMASARAN TERHADAP KUALITAS PRODUK PAKAN TERNAK PADA CV. DALIJO ULAM UPADI DI MUARA BADAK - Aswardin; Ilham; Akhmadiansyah (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2023)
CV. Dalijo Ulam Upadi feels that he has not reached the sales volume according to the target, which is affecting the company's income. Apart from that, product quality is often less than optimal in processing because the raw materials the company receives are sometimes not good or only a small amount. so the fear of producers is that it can make livestock less healthy when consumed so that it can make livestock less healthy, this most often happens because the raw material for making fertilizer is made from pure fish, this causes a decrease in production due to a lack of fish supply to the company, this can also causing the company to suffer losses or lose consumers so that consumers look for animal feed from other competitors. The aim of this research is to find out what factors influence the quality of animal feed products at CV. Dalijo Ulam Upadi in Muara Badak. This research uses a quantitative approach, the sample used is all CV employees. Dalijo Ulam Upadi in Muara Badak, numbering 27 people. Then the data uses the factor analysis method. The results of this research are based on the calculations obtained where the results of the calculations obtained as a whole are declared to have met the requirements, meaning that the first hypothesis proposed is that there are marketing performance factors on the quality of animal feed products at CV. Dalijo Ulam Upadi was accepted because it was proven to be true. The second hypothesis proposed was that the factor that the proposed hypothesis is accepted because it is proven to be true.